COLLOID-CHEMICAL PATTERNS OF SORPTION OF PALLADIUM (II) ON PHYTOSORBENTS: UDC 544.723+543.3+546.9 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
The colloid-chemical patterns of sorption of palladium (II) on phytosorbents have been studied. It was found that the kinetics of sorption depends on the concentration of palladium (II) in the solution. When the concentration increases, the time of the establishment of the sorption equilibrium increases. Kinetic curves are best described by a pseudo-second order model throughout the range of concentrations studied.The correlation coefficient in the pseudo-first order equation at high concentrations of palladium (II) in the solution has a value close to 1.This feature may indicate that, at low concentrations, the chemical interaction between the metal ion and the functional group of sorbent prevails.At the same time, at high concentrations, internal diffusion also contributes.Thus we have two types of surface groups: "fast" – are on the surface of the sorbent and "slow" – located in the deep layers of the sorbent, access to which is complicated.To corroborate this assumption, the palladium (II) sorption isotherms were constructed on the surface of the phytosorbent at different times of the phase contact.With increasing time of phase contact increases sorption capacity.An increase in temperature leads to an increase in sorption capacity and a decrease in the time of the establishment of sorption equilibrium.This influence of temperature is probably due to the fact that the diffusion of metal ions is accelerated and in the chemisorption immediately, both "fast" and "slow" groups of sorbent are involved.The experimental isotherms of sorption are analyzed using the theoretical models of Langmuir and Freundlich adsorption.It was established that the isotherms of adsorption of palladium (II) on the surface of the phytosorbent are best described by the Langmuir model.The Freundlich model is not suitable for describing the palladium adsorption (II), since the experimental points do not lie straight, and the correlation coefficient has low values.It has been shown that phytosorbent exhibits a good kinetic property and has a high sorption capacity in relation to palladium (II).
Keywords: electronic nose, probabilistic neural network, identification, cooked sausages